Religion, spirituality and patient counselling: a scoping review - Abu Hanifah, Nabihah; Ramlan, Husna Kauthar; Mohammad Za'aim, Adhwa Diyanah; Nor Azmi, Anis Suzanna; Ahmad Azam, Faizah Hanani; Zahari, Noor Amirah; Maslil, Nor Aisyah; Zaini, Syahrir (Kulliyyah of Pharmacy, International Islamic University Malaysia (IIUM), 2021)
Religion and spirituality (R/S) have immense potential in influencing the effectiveness of patient counselling in the healthcare setting. Although substantial literature has studied the relation of religion, spirituality and health, a limited number of studies have investigated the effect of religious/spiritual practices in patient counselling. This study aims to review available qualitative research on the outcome of practising religion and spirituality in patient counselling through scoping review.